Radiotherapy-Induced Malignancies: Review of Clinical Features, Pathobiology, and Evolving Approaches for Mitigating Risk - Braunstein, Steve; Nakamura, Jean L. (Frontiers in Oncology, 2013)
One of the most significant effects of radiation therapy on normal tissues is mutagenesis, which is the basis for radiation-induced malignancies. Radiation-induced malignancies are late complications arising after radiotherapy, increasing in frequency among survivors of both pediatric and adult cancers. Genetic backgrounds harboring germline mutations in tumor suppressor genes are recognized risk factors. Some success has been found with using genome wide association studies to identify germline polymorphisms associated with susceptibility. The insights generated by genetics, epidemiology, and the development of experimental models are defining potential strategies to offer to individuals at risk for radiation-induced malignancies. Concurrent technological efforts are developing novel radiotherapy delivery to reduce irradiation of normal tissues, and thereby, to mitigate the risk of radiation-induced malignancies. The goal of this review is to discuss epidemiologic, modeling, and radiotherapy delivery data, where these lines of research intersect and their potential impact on patient care.